Governance of physical learning environment design in a decentralized policy context - Siv Marit Stavem (Nordic Journal of Studies in Educational Policy)
School buildings worldwide have given voice to educational purposes and have been employed as policy instruments. This article outlines a study concerning governance of the design of the physical learning environments in a decentralized policy setting. Based on document analysis of three design briefs and interviews with key persons for local school design in three local governments, this article seeks to explore how central policy imperatives and regulations are enacted in local school design. By deploying the concepts of translation and path dependence as analytical tools, the paper highlights how laws and regulations on school buildings’ design are transformed in local settings. The concepts of loose and tight couplings are deployed to investigate how organizations are tied together. This paper demonstrates strong regulations from the health authorities and building authorities which were enacted by translations into the design briefs. Weak regulations were demonstrated through the absence of the central education authorities in the developments of school buildings. This paper argues that local governments had a concern for good physical environments for both learning and health for their students; however, the central education authorities were absent in the discussion, leaving students’ physical learning environment to a matter of health and well-being.